PERSEPSI MAHASISWA PPKN UNIVERSITAS RIAU TERHADAP PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 21 TAHUN 2020 TENTANG PEMBATASAN SOSIAL BERSKALA BESAR DALAM RANGKA PERCEPATAN PENANGANAN CORONA VIRUS DISEASE (COVID-19) - Maulina Oktriananda; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the issuance a Republic of Indonesia Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease (COVID-19). The formulation of the problems in this research is how perception of PPKn students Universitas Riau towards the Republic of Indonesia Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease (COVID-19). The purpose of this research is to find out perception of PPKn students Universitas Riau towards the Republic of Indonesia Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease (COVID-19). The research method is descriptive quantitative. Based on the result of the research, it is found that the result of the calculation of respondents who answered “Agree” amounted to 71.5% where this range is in “Good” with a presence of 66.67% – 100%. Perception of PPKn students Universitas Riau towards the Republic of Indonesia Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease (COVID-19) are “Good”.Key Words: Perception, Students, Government Regulation, PSBB